2000
DOI: 10.1161/01.cir.102.suppl_3.iii-352
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tumor Necrosis Factor-  and Interleukin-6 in Myocardium and Serum of Malfunctioning Donor Hearts

Abstract: Background-Myocardial dysfunction is a common and important problem in donor hearts. The mechanisms responsible remain unclear. We have studied the cytokines tumor necrosis factor (TNF)-␣ and interleukin-6 (IL-6) in the myocardium and serum from donors with myocardial dysfunction (unused donors) and compared them with donors with good ventricular function (used donors) and patients with advanced heart failure (HF). Methods and Results-Clinical details and ventricular function were assessed in 46 donors (31 use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 25 publications
1
85
0
1
Order By: Relevance
“…[47][48][49][50] Increased expression of IL-6 and TNF-a has been related to malfunction of donor hearts and prediction of right ventricular failure after human heart transplantation. 51,52 In kidney transplantation, both short-and long-term results of unrelated living transplants are superior to even well-matched cadaveric transplants, [53][54][55] and increased cytokine levels in the blood and kidney of brain-dead donors compared with living donors reflect this difference in outcome between living and cadaveric donation. 47 Cytokines have many effects, both synergistic and antagonistic, on the immune system.…”
Section: Inflammatory and Immunological Aspects Of Brain Deathmentioning
confidence: 99%
“…[47][48][49][50] Increased expression of IL-6 and TNF-a has been related to malfunction of donor hearts and prediction of right ventricular failure after human heart transplantation. 51,52 In kidney transplantation, both short-and long-term results of unrelated living transplants are superior to even well-matched cadaveric transplants, [53][54][55] and increased cytokine levels in the blood and kidney of brain-dead donors compared with living donors reflect this difference in outcome between living and cadaveric donation. 47 Cytokines have many effects, both synergistic and antagonistic, on the immune system.…”
Section: Inflammatory and Immunological Aspects Of Brain Deathmentioning
confidence: 99%
“…These events may have important therapeutic implications. 54) Inhibition of IL-6 secretion in cardiac transplant recipients is an important factor to protect against the development of cardiac allograft vasculopathy. HMG-COA reductase is reported to inhibit IL-6 secretion.…”
Section: )mentioning
confidence: 99%
“…In the donated heart study by Birks et al (96 ), a trend was noted for higher IL-6 concentrations in the hearts not used in transplantation [16.5 (2.9) ng/L] compared with 13.9 (1.6) ng/L in the hearts used. The IL-6 mRNA concentration was also more than twofold greater in the unused hearts than in the hearts actually suitable for transplantation (96 ). In another cohort of Ͼ140 heart transplantations, plasma concentrations of TNF-␣ and IL-6 were shown to increase before the appearance of histologic signs of rejection (101 ).…”
Section: Mechanism Of Release In Hfmentioning
confidence: 95%
“…In particular, increased serum concentrations of IL-6 or its expression in the heart can serve as a biomarker of myocardial function. It has also been suggested that pharmacologic modulation of cytokine production in donor hearts can improve the probability that the donated hearts will be used in transplantation (96 ).…”
Section: Mechanism Of Release In Hfmentioning
confidence: 99%